ICT, corporate restructuring and productivity - Laura Abramovsky; Rachel Griffith (Institute for Fiscal Studies (IFS), 2009)
Stronger productivity growth in the US than the EU over the late 1990s is widely attributed to faster, more widespread adoption of information and communication technology (ICT). The literature has emphasised complementarities in production between ICT and internal restructuring as an important mechanism. We investigate the idea that increased use of ICT has facilitated outsourcing of business services, and that these are complementary activities in production because they allow firms to focus on their core competencies. This is consistent with evidence from the business literature and aggregate trends, and we show evidence from microdata that is consistent with this idea.
Keywords: D2; O3; O4; 330; ICT; outsourcing; productivity; Betriebliche Investitionspolitik; Reorganisation; Informationstechnik; Outsourcing; Produktivität; Großbritannien